Epidemiology and clinical characteristics of thyroid dysfunction in children and adolescents with type 1 diabetes - Severinski, Srećko (Array, 2009)
Abstract: The aim of the study was to evaluate the natural course and potential risk factors of autoimmune thyroiditis (AIT) and thyroid dysfunction, and their influences on growth and glycemic control in children and adolescents with type 1 diabetes mellitus (T1D). The study comprised 148 subjects (age range 1–21 years; males 51%) with T1D. During the interval of 12 years serum levels of thyroid peroxidase (anti-TPO) and thyroglobulin (anti-TG) autoantibodies, thyroid-stimulating hormone (TSH) and tyroksine (T4), were screened annually. Height, weight, body mass index (BMI), glycosylated hemoglobin (HbA1c), insulin dose and the number of severe hypoglycemic episodes, were recorded every 3 months.The mean folow-up was 7 ± 4.1 years. Prevalence of AIT in subjects with T1D was 15.5%. It was significantly higher in girls (21.9% vs. 9.3%; p=0.03). The mean age at AIT onset was 11.5 ± 5.2 years. The mean interval between negative and positive AIT screening was 2.5 ± 2.3 years.